1990
DOI: 10.1177/014860719001400511
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, Membrane Receptors, and Enzymes: Effects of Dietary Fatty Acids

Abstract: Dietary polyunsaturated fatty acids can significantly affect many biochemical and physiologic functions that are related to inflammatory, immune, and protective reactions. The different types of fatty acids can impact on energy metabolism, determine the lipid composition of membranes, and influence eicosanoid synthesis, all of which are relevant to prevention of and recovery from illness. In this paper, the effects of dietary polyunsaturated fatty acids on membrane composition, membrane-associated enzyme and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 63 publications
2
43
0
4
Order By: Relevance
“…The low concentrations of plasma PL may have limited the availability and subsequent incorporation of these fatty acids into cell membranes (Chapkin et al, 1988) or supplemented fatty acids may have been directed to oxidative pathways (Korber et al, 1999;Zuijdgeest-van Leeuwan et al, 2000) rather than incorporated into cellular membranes. The capacity to impact on immune functions by altering membrane fluidity, enzyme activities and intracellular signals (Traill and Wick, 1986;Sakata et al, 1987;Graber et al, 1994;Peck, 1994b;de Pablo and Alvarez de Cienfuegos, 2000) through nutritional supplementation is assumed to be dependent on incorporation of supplemented fatty acids into membranes (Russell et al, 1987;Kinsella, 1990;Lester, 1990;Peck, 1994a) and the optimal conditions of supplementation for this to occur are presently unknown. Therefore, obstacles exist that must be addressed in future trials aiming to alter immune functions through lipid supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The low concentrations of plasma PL may have limited the availability and subsequent incorporation of these fatty acids into cell membranes (Chapkin et al, 1988) or supplemented fatty acids may have been directed to oxidative pathways (Korber et al, 1999;Zuijdgeest-van Leeuwan et al, 2000) rather than incorporated into cellular membranes. The capacity to impact on immune functions by altering membrane fluidity, enzyme activities and intracellular signals (Traill and Wick, 1986;Sakata et al, 1987;Graber et al, 1994;Peck, 1994b;de Pablo and Alvarez de Cienfuegos, 2000) through nutritional supplementation is assumed to be dependent on incorporation of supplemented fatty acids into membranes (Russell et al, 1987;Kinsella, 1990;Lester, 1990;Peck, 1994a) and the optimal conditions of supplementation for this to occur are presently unknown. Therefore, obstacles exist that must be addressed in future trials aiming to alter immune functions through lipid supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the production of these enzymes can be partially responsible for the protective effect of antioxidants (Health, 1995). Numerous functions related to membranes lipids are important for the immunological system and the blood platelets, as well as for their association with specific glycoproteins of the cell wall (Kinsella, 1990). The amounts of arachidonic acids and/or their competitors (PUFAs) released after membrane stimulation, via conversion to eicosanoids, have wide reflexes or effects on physiologic functions .…”
Section: $%675$and7 )Xqfwlrqdo Irrg Suhvhqwv Vshflilf Sk\vlrorjlfdo Surmentioning
confidence: 99%
“…The ω-3 PUFAs are rapidly depleted from most tissues following cessation of feeding (Swanson et al 1986). Several researches have shown that diets rich in fat may be associated with an increase in the incidence, accelerated growth and development of certain tumors (Cave, 1991;Kinsella, 1990). In view of this fact, studies have been carried out to determine the capability of numerous families of fatty acids to promote tumors growth.…”
Section: %Hqhilfldo Hiihfwv Ri 38)$vmentioning
confidence: 99%
“…grades in the fish oil group might be because of an incorporation of adequate amounts of EPA and DHA into the phospholipid bilayer of the graft tissue, resulting in a modification of membrane fluidity, intracellular signal transduction, production of less harmful eicosanoids, less proinflammatory cytokine release, and reducing cytokine receptor interaction. The net outcome of these events will be reduced T-cells recruitment and the extent of inflammation (2,26). Neither fish oil nor Values represent means Ϯ SD (n ϭ 5 to 6 animals).…”
Section: Discussionmentioning
confidence: 99%